10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Plain Language SummaryInterpreting autism and gender dysphoria findings carefully in a referred clinic samplePascoe and colleagues studied adults referred to a gender identity clinic and compared people with and without a recorded autism diagnosis. Their study raises important questions about how autism, gender-related distress, and mental health difficulties may overlap in people seeking care. This letter argues that the findings should be interpreted with caution. The study relied on autism diagnoses already recorded in medical charts, rather than confirming autism through a structured assessment. This means some autistic people may have been missed, while others may have been more likely to have autism documented because they had more complex mental health histories. Either situation could affect the comparison between groups. The letter also notes that the study reports many statistical comparisons, so some results may need more cautious interpretation. The largest and most clinically important finding may not be the difference in gender dysphoria diagnosis, but the higher burden of mental health and neurodevelopmental difficulties in the group with recorded autism. Overall, the letter does not argue against care for autistic gender-diverse adults. Rather, it emphasizes that when autism, mental health difficulties, and gender-related distress overlap, clinicians should take time to understand each person's individual situation before drawing conclusions about the most appropriate care pathway.